Towards a Shared Vision of the Climate Security Nexus in Senegal: A joint report to inform the National Climate Change Action Plan for Senegal - Sarzana, Carolina; Cisse, Sokhna Ramatoulaye; Medina, Leonardo; Jaquet, Stéphanie; Madurga Lopez, Ignacio M.; Schapendonk, Frans; Touré, Oussouby; Tall, Laure; Dimanche, Pierre-Henri; Diatta, Lamine; Dièye, Bounama; Ouédraogo, Issa; et al. (CGIAR Initiative on Climate Resilience, 2022)
This report explores the complex climate-security nexus in Senegal while documenting on the Climate Security Workshop, held in Dakar in October 2022. The Climate Security workshop, organized as part of the CGIAR’s initiative Building Systemic Resilience against Climate Extremes and Variability (ClimBeR) and co-hosted by the African Group of Negotiators Experts Support (AGNES), brought together actors involved with either climate and security issues in Senegal, and more broadly in the Sahel, to discuss Senegal's security architecture and its relationship with climate. The aim of the workshop was to inform national and sub-national policies and investments to build agricultural resilience and foster climate-resilient peace. Through three facilitated focus group discussions, the different stakeholders working around climate and security issues shared their experiences of how climate impacts influence the environmental, social, economic, and political processes that lead to conflict and insecurity.